Inequalities in health and health behaviours between couple and lone mothers before and during the financial crisis in Spain (2003-2012) - Sara Trujillo-Alemán; Glòria Pérez; Vanessa Puig-Barrachina; Mercè Gotsens; Jillian Reynolds; Silvia Rueda; Carme Borrell (Elsevier, 2019)
Lone mothers report worse health and adopt more risky health behaviours than couple mothers, as largely documented in several European countries, but not deeply in Spain. The primary aim of this study was to identify the possible existence of inequalities in health and health behaviours between couple and lone mothers in Spain by occupational social class and employment status. A second aim was to explore whether any inequalities were influenced by the economic crisis beginning in 2008, analysing changes in inequalities between 2003-2004 and 2011-2012.Two waves of the cross-sectional Spanish National Health Survey data were used. Analyses were restricted to mothers aged 16-64 years, with at least one child aged 18 years or younger. The sample consisted of 2982 mothers in 2003-2004 and 3070 in 2011-2012, representing more than 80% of couple mothers. Two health outcomes and two health behaviour measurements were used. Robust Poisson regression was run to estimate inequalities between couple and lone mothers, calculating prevalence ratios adjusted by age and stratified by social class and employment status.We found inequalities in health and health behaviours between couple and lone mothers in Spain amongst the manual social class, with lone mothers reporting a more than 30% higher prevalence of poor self-perceived health and being smoker in both time points of study compared with couple mothers. Furthermore, lone mothers were at 50% higher risk of having at least one selected chronic condition and 86% higher probability of sleeping less than 6 hours/day in 2011-2012 This study could not confirm that inequalities between couple and lone mothers changed in Spain during the study period, although some patterns were noticeable. Inequalities pointed towards an increase amongst mothers in the manual social class with paid employment, while inequalities amongst unemployed mothers (both manual and non-manual social class) pointed towards a decrease. Keywords: Spain, Lone mothers, Health inequalities, Health behaviours, Crisis, Social class